V.2 - Couto, Richard A. (ed.) (New Delhi, 2010)
This title, within The SAGE Reference Series on Leadership will provide undergraduate students and academics with an authoritative reference resource on political and civic leadership. This two-volume set will be centred on the 100 most important topics, issues, questions and debates specific to politics and civic society. This focus will provide students with more detailed information and depth of discussion than typically found in an encyclopedia entry but not as much jargon, detail or density as a journal article or a research handbook chapter. Chapters will cover key topics related to political and civic leadership including: personalities and environments of political leaders governance and allegiance roles citizen activists and civic engagement political campaigning urban politics and leadership public management ethics in politics policy development and implementation executive management of public opinion political speechmaking and the "bully pulpit" Congressional leadership crisis management.
Keywords: Political leadership